Topics in Mathematical Fluid Mechanics Cetraro, Italy 2010, Editors: Hugo Beirão da Veiga, Franco Flandoli - Constantin, Peter; Debussche, Arnaud; Galdi, Giovanni P.; Růžička, Michael; Seregin, Gregory (C.I.M.E. Foundation Subseries ;, 2013)
This volume brings together five contributions to mathematical fluid mechanics, a classical but still very active research field which overlaps with physics and engineering. The contributions cover not only the classical Navier-Stokes equations for an incompressible Newtonian fluid, but also generalized Newtonian fluids, fluids interacting with particles and with solids, and stochastic models. The questions addressed in the lectures range from the basic problems of existence of weak and more regular solutions, the local regularity theory and analysis of potential singularities, qualitative and quantitative results about the behavior in special cases, asymptotic behavior, statistical properties and ergodicity.